Methamphetamine Compromises the Adaptive B Cell-Mediated Immunity to Antigenic Challenge in C57BL/6 Mice - Mitha, Anum N.; Chow, Daniela; Vaval, Valerie; Guerrero, Paulina; Rivera-Rodriguez, Dormarie E.; Martinez, Luis R. (Frontiers in Toxicology, 2021)
Methamphetamine (METH) is a substance of abuse that causes dysregulation of the innate and adaptive immunity in users. B cells are involved in the humoral component of the adaptive immunity by producing and secreting antibodies (Abs). METH modifies Ab production, although limited information on the impact of this psychostimulant on antigen (Ag)-specific humoral immune responses is available. Since T cell-dependent and T cell-independent Ags are involved in the activation of B lymphocytes, we explored the role of METH on humoral immunity to ovalbumin (OVA; T cell-dependent) and bacterial lipopolysaccharide (LPS; T cell-independent) in C57BL/6 mice. We demonstrated that METH extends the infiltration of B cells into pulmonary and splenic tissues 7 days post-Ag challenge. METH impairs Ab responses in the blood of animals challenged with OVA and LPS. Furthermore, METH diminishes the expression and distribution of IgM on B cell surface, suggesting a possible detrimental impact on users’ humoral immunity to infection or autoimmunity.